2021
DOI: 10.3390/s21217233
|View full text |Cite
|
Sign up to set email alerts
|

Atrial Fibrillation Classification with Smart Wearables Using Short-Term Heart Rate Variability and Deep Convolutional Neural Networks

Abstract: Atrial fibrillation (AF) is a type of cardiac arrhythmia affecting millions of people every year. This disease increases the likelihood of strokes, heart failure, and even death. While dedicated medical-grade electrocardiogram (ECG) devices can enable gold-standard analysis, these devices are expensive and require clinical settings. Recent advances in the capabilities of general-purpose smartphones and wearable technology equipped with photoplethysmography (PPG) sensors increase diagnostic accessibility for mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 62 publications
1
13
0
Order By: Relevance
“…However, assessment of different AF classes remains limited, pioneered by field studies [29,50] separating AF into chronic (ChAF) and paroxysmal (ParAF). Throughout reviewed studies, the research efforts put on device-oriented and field data progress deserve special credit [25,47,49,72] regardless of the not yet remarkable performances achieved, as only the fully ambulatory approaches (online processing) that achieve success would enable future development of pacemaker-like medical devices capable of reverting AF attacks to normal rhythms. While the low computational demands of the RR-based univariate methods offer a bright future in the domain of wearables with limited but increasing computational capabilities, the interconnected IoT Cloud and services that are emerging in remote health markets may be calling for a research look at a wide range of multivariate pretrained models with renewed interest.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, assessment of different AF classes remains limited, pioneered by field studies [29,50] separating AF into chronic (ChAF) and paroxysmal (ParAF). Throughout reviewed studies, the research efforts put on device-oriented and field data progress deserve special credit [25,47,49,72] regardless of the not yet remarkable performances achieved, as only the fully ambulatory approaches (online processing) that achieve success would enable future development of pacemaker-like medical devices capable of reverting AF attacks to normal rhythms. While the low computational demands of the RR-based univariate methods offer a bright future in the domain of wearables with limited but increasing computational capabilities, the interconnected IoT Cloud and services that are emerging in remote health markets may be calling for a research look at a wide range of multivariate pretrained models with renewed interest.…”
Section: Discussionmentioning
confidence: 99%
“…Addressing the problem of Paroxysmal AF detection in 5-min HRV segments, performance achieved values of 80.4% and 89% sensitivity and specificity, respectively, in a system trained by the Paroxysmal Atrial Fibrillation Prediction Challenge data that is tested with a combination of NSRDB and AFDB HRV sequences including Paroxysmal AF cases from the latter. In the work of Ramesh et al [72], important progress is shown in moving ECG-based AF detection methods to photoplethysmography-equipped remote health tracking devices. Although still falling short in performance with respect to benchmark tests on databases, partly due to class imbalance for the device acquired data, this work successfully paves the way for future transfer knowledge directions.…”
Section: Application Of Multivariate Data Analysis On Rr Time Seriesmentioning
confidence: 99%
“…Concerning diagnosis from a one-lead ECG recording, Hannun et al showed a superior accuracy of a DNN compared with board-certified cardiologists [ 28 ], which furthermore extended to other arrhythmias such as regular supraventricular tachycardia and atrioventricular block. Unifying applications across different diagnostic modalities, Ramesh et al recently reported the development of a DNN able to detect AF with a high diagnostic accuracy in both ECG and photoplethysmographic recordings [ 29 ]. Importantly, neural networks can also aid the screening for AF even when it is absent at the time of presentation.…”
Section: Clinical Applicationsmentioning
confidence: 99%
“…While there is still limited supporting evidence for systematic screening for AF, as well as associated cost implications [26], targeted screening, systemic opportunistic screening or smartphone algorithms, may be a more cost-effective option when using AI-enhanced ECG systems. With an increasing consumer adoption of wearable healthcare technologies [27,28], the incorporation of AIenhanced algorithms for AF screening [29][30][31][32] would be expected to AF-related morbidities in the long-term [33,34].…”
Section: Cardiovascular Diseasementioning
confidence: 99%